(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Pramono S. 2025. Field-laboratory assessment of predatory response of Chilocorus melanophthalmus and Scymnus sp. against Aulacaspis tegalensis (Hemiptera: Diaspididae) infestation on sugarcane. Biodiversitas 26: 4057-4064. Sugarcane production in Indonesia is significantly affected by pest infestations, among which the sugarcane scale insect (Aulacaspis tegalensis) is particularly destructive due to its ability to reduce both crop yield and quality. This study aimed to evaluate the potential of natural enemies as biological control agents for A. tegalensis to provide a more sustainable alternative. Field and laboratory experiments were conducted from April 2021 to September 2022 in sugarcane plantations in Central Lampung, Lampung, Indonesia. Field experiments, arranged in a randomized block design, monitored predator-prey interactions and measured predator attack rates on A. tegalensis. Laboratory experiments, using a completely randomized design, evaluated predation at prey densities of 10-320 individuals with two predator species, Chilocorus melanophthalmus and Scymnus spp.. The results showed that C. melanophthalmus and Scymnus spp. had moderate positive correlations with A. tegalensis population densities in the field (correlation coefficients r: 0.51 and 0.41, respectively; p<0.05). Their average predation rate for C. melanophthalmus was 4-10 prey individuals per day, and for Scymnus spp. 4-9 prey individuals per day that which are indeed promising biological control agents. Laboratory tests indicated that these two predators exhibited a type II functional response, meaning that their predation rate increased with prey density but eventually reached a saturation point due to handling time constraints. Both predators showed strong dependency on prey density (r: 0.73 and 0.82), indicating high predation potential. Conversely, C. nigritus and Telsimia spp. showed weaker responses and limited predation efficiency. These findings suggest that C. melanophthalmus and Scymnus spp. are promising biological control agents for managing A. tegalensis infestations in sugarcane plantations, instilling confidence in the future of sustainable pest management. Integrating these predators into integrated pest management strategies could reduce reliance on chemical insecticides, lowering environmental risks and supporting sustainable sugarcane production in Indonesia.